Synthesis and Characterization of DOPO Modified Tetraglycidyl Eugenol Cyclic Siloxane Resins Cured with Tannic Acid - Rusheni B. Senanayake; Houlei Gan; Dan Liu; Asanka P. Basnayake; Michael T. Heitzmann; Russell J. Varley (Macromolecular Materials and Engineering)
Abstract In this work, a tetra glycidyl eugenol cyclic siloxane resin (TGED4) is synthesized, then further modified with 9,10‐dihydro‐9‐oxa‐10‐phosphaphenathrene‐10‐oxide (DOPO) to produce Si and P epoxy resins. After blending with diglycidyl ether of bisphenol A (DGEBA) and curing with tannic acid (TA), high performance, fire‐retardant polymer networks are created. Near infrared spectroscopy (NIR) confirms the networks are highly cured and have low extractable content, while dynamic mechanical thermal analysis (DMTA) displays a lower Tg and heterogeneous network with increasing DOPO. The networks display a maximum improvement in flexural modulus, strength, and strain to failure of 20.6%, 55.5%, and 78.8% respectively, and at 65.4 MPa strength and 2.8 GPa modulus are comparable to high‐performance networks. Thermogravimetric analysis (TGA) shows that increasing P reduces thermal stability, but contributes to higher char yield despite lower Si. The fire retardancy improve markedly measured via limiting oxygen index (LOI), increasing from 26.5% to a maximum of 35.5%, while V‐0 behavior is readily achieved at the lowest DOPO content. Cone colorimetry further reduces peak heat release rate (PHHR) and total heat release rate (THHR) by 28% and 42%. This work presents hybrid bio‐derived epoxy resins with excellent fire retardancy and good mechanical properties.